STRATEGIES FOR IMPROVING SUPPLY CHAIN MANAGEMENT IN THE OIL INDUSTRY IN NIGERIA: A Case Study of Nigerian National Petroleum Corporation. - Umuerri, O. Efemena (2013)
Purpose – The purpose of this research is to explore the challenges faced in the oil supply chain in a developing country like Nigeria and subsequently, provide recommendations on ways to improve the competitiveness of the oil industry.